QSAR analysis of SH2-binding phosphopeptides: Using interaction energies and cross-correlation coefficients - Moon, T; Song, JS; Lee, JK; Yoon, CN (AMER CHEMICAL SOC, 2003)
Quantitative structure-activity relationships (QSAR) analyses were carried out on the SH2-phosphopeptide complexes using multiple linear regressions. The residue-residue interaction energies and cross-correlation coefficients were used as descriptors. Since the number of descriptors was very large (602 for interaction energies and 951 for cross-correlation coefficients), the stepwise addition method was applied for the multiple linear regressions. The residue-residue interaction energies were good descriptors for structure-activity relationships. The high r(2) regression models were achieved by using interaction energy. In addition, the concerted atomic motions, which show the dynamic properties during the SH2-phosphopeptide interaction, were used as descriptors. They were identified by the cross-correlation coefficients for atomic displacement. The best regression model, derived by using four cross-correlation coefficients, gave a high r(2) value of 0.925. This suggests that the dynamic properties showing concerted atomic motions can be used as good descriptors in QSAR study.
Keywords: AFFINITY PHOSPHOTYROSYL PEPTIDE; SH2 DOMAIN; SIGNAL TRANSDUCTION; CRYSTAL-STRUCTURES; PROTEIN-KINASE; BINDING; RECOGNITION; PP60C-SRC; P56(LCK); FAMILY